Kuningas Salomon kaivokset - Haggard, H. Rider (Henry Rider), 1856-1925 (Salt Lake City, UT : Project Gutenberg, 2017)
"Kuningas Salomon kaivokset" by H. Rider Haggard is a novel published in 1885. Allan Quatermain leads an expedition into unexplored Africa to find a missing aristocrat's brother and the legendary mines of King Solomon. The group faces deadly deserts, treacherous mountains, and a brutal African kingdom ruled by a murderous usurper. To survive, they must pose as gods while navigating witch hunts, tribal warfare, and ancient secrets that could cost them their lives. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/King_Solomon%27s_Mines
Release date is 2017-05-19
E-text prepared by Timo Ervasti and Tapio Riikonen
Keywords: Africa -- Fiction; Missing persons -- Fiction; Adventure stories; Treasure troves -- Fiction; Hunting guides -- Fiction; Diamond mines and mining -- Fiction; Quatermain, Allan (Fictitious character) -- Fiction